Efektivitas Pendekatan Teaching at the Right Level (TaRL) terhadap Hasil Belajar Bahasa Indonesia pada Materi Paragraf Deskripsi Siswa Kelas IV SDN Pedurungan Kidul 01 - Darmawan Adi Wiguna; Duwi Nuvitalia; Fitria Miftakhul Jannah (Departement of Mathematics Education, 2025)
Students' difficulties in writing description paragraphs in elementary school are often caused by disparities in abilities between students, which can hinder effective learning. The Teaching at the Right Level (TaRL) approach can be an alternative solution to overcome this problem by grouping students based on their ability level. This study aims to measure the effectiveness of the TaRL approach in improving student learning outcomes in the description paragraph material in grade IVB SDN Pedurungan Kidul 01. The method used is a pre-experiment design with a mixed method approach, combining quantitative data through pretest and posttest analyzed using the Paired Sample T-Test and N-Gain tests, as well as qualitative data through observation of the learning process. The results showed a significant improvement in learning outcomes, with the average pretest score increasing from 46.43 to 72.14 in the posttest. The Paired Sample T-Test produced a significance value of 0.000 < 0.05, showing a significant influence. Based on the N-Gain test, the effectiveness of the TaRL approach on student learning outcomes is in the medium category (0.5049). Qualitatively, the application of the TaRL approach also increases student motivation, engagement, and independence. In conclusion, the TaRL approach has proven to be effective in improving student learning outcomes and creating learning that is inclusive and in accordance with the individual needs of students.